(3fhQ GdQhVs - (3fhQGdOjf eMeO Hf EHQGgje Hf LeGYg GdcfGfi GdYSbdGfis ((3YHOGddg Hf eMehO s)
(3ChdgG (B:s
(3Chd eG ajgG ef CKfGA GdcdGe Ydi ehdOg Udi Gddg Ydjg hSde s
(3LRAGf ai eLdOs
(3gh eNJUQ cJGH GdQhV GdCfa ddSgjdi GdPi TQM ajg SjQI QShd Gddg dGHf gTGes
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs